EVALUATION OF DIFFERENT LEVELS OF Anogeissus leiocarpus LEAVES AND WHEAT OFFALS ON GROWTH PERFORMANCE AND HAEMATO-BIOCHEMICAL PARAMETERS OF YANKASA SHEEP - Muhammad, U.; Ahmed, A.; Bah, S. U. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was conducted to evaluate different levels of Anogeissus leiocarpus and wheat offals on the growth performance and haemato-biochemical parameters of growing Yankasa rams. Four diets (16% protein) were formulated using varying levels of African birch (Anogeissus leiocarpus) at 0, 10, 20 and 30% in the diets and termed as diets 1, 2, 3 and 4 respectively. Twenty (20) growing Yankasa rams with average body weight of 17.2kg were allocated to 4 treatments groups of five (5) animals each in a completely randomized design. Total feed intake differed significantly (P<0.05) among the treatments, with treatments 2 and 4 having the highest values of 1057.98g/day and 1051.53g/day followed by 1035.24g/day and 1006.97g/day for T3 and T1 respectively. The result also revealed that weight gain differs significantly (P<0.05) across the diets with animals on treatment 2 recording the highest value (126.19g/day) compared to 59.52, 59.52 and 88.90g/day for diets 1. 3 and 4 respectively. Feed conversion ratio (FCR) values were significantly (P>0.05) different across the treatments with animal fed diet 2 recording the best FCR, (7.33) followed by those on treatment 4 (10.29). Animal on treatment land 3 recorded lowest FCR values of 15.05 and 15.12 respectively. Crude protein digestibility (CPD) results revealed that all the diets had higher and similar CPD (88.70 to 89.70) values. All the haematological and biochemical values obtained for all parameters across the treatments fell within the normal values for healthy rams. From the result of this study diet 2 (10% AL/20%WO) which gave the best average daily weight gain (126.19g/day) and the best utilized diet (7.33) can be recommended for growing Yankasa rams.